1910 Colombian constitutional reform and the electoral system (1910-1914) - Acuña Rodríguez, Olga Yanet (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In 1910 in Colombia a constitutional reform took place. It was promulgated through Legislative Act 03 and its aim was to strengthen the development of democracy, as a strategy for mediating the bipartisan conflict that Colombian society had been living through since the XIX century. Therefore, governments needed to be legitimated periodically and systematically through the ballot box. Although the elections were not enough to define a democratic political system,  they were associated with the expression of representative democracy. The objective of this work is to analyze in what way the constitutional reform was intended to introduce an electoral system that would allow the elites to solve the problems of governability and representation, without significantly expanding the number of voters. The study of the elections is mainly carried as from political history, which allows for the analysis of how the constitutional reform was a strategy of the elites to reorganize the political and economic context after the thousand-day war (1898-1902), and thus avoid the development of a new conflict. Through the constitutional reform, representative democracy, centered on elections as a mechanism for legitimating power, was called for, and a new form of electoral organization was established which had its center in the capital of the country and from there links were made to the processes carried out in the departments and municipalities.